Champions of Equity: Fostering Civic Education to Challenge Silence, Racial Inequity, and Injustice. (3rd April 2019) - Samuels, Amy J.; Samuels, Gregory L.; Self, Christopher
Abstract : This article presents a study that explored how race and racism impact teaching and learning and how civic education can be employed to promote racial justice. We argue the need to examine educators' perspectives on how increased awareness of existing inequities coupled with ongoing professional development can better equip them to understand their identity, engage in meaningful dialogue, and teach in culturally responsive ways. The paper concludes with a brief discussion of teaching implications related to self-assessment, disruptive discourse, and inclusive practices.